Evolution Mechanism of Deformation and Failure of Surrounding Rock during Excavation and Unloading of the High-Stress Rock Mass - Wensong Xu; Guangming Zhao; Chongyan Liu; Xiangrui Meng; Ruofei Zhang; Siming Kao; Shunjie Huang; Jun Zhou; Rui Peng (Advances in Civil Engineering)
To deeply analyze the failure evolution of surrounding rock during excavation-induced unloading of the high-stress rock mass, a multistage failure model was established based on revealed failure patterns. The critical conditions for wing cracks were determined. The slab crack buckling analysis was carried out. The true-triaxial rockburst testing system was used for the miniature model test to study the fracturing evolution of surrounding rocks during excavation-induced unloading of the high-stress rock mass. The research results indicated that harder rock samples had higher compressive strength. Moreover, the smaller peak strains implied more obvious yield/plastic stages of harder rock samples with high confining pressures and softer rock samples with low confining pressures. V-shaped grooves appeared at the beginning of the surrounding rock’s failure while spalling and splitting occurred as the stress increased. Finally, the entire sample’s overall splitting failure was observed, and the borehole bottom bulged upward. The harder rock masses had fewer fractures and higher degrees of failure. There were obvious V-shaped grooves on both sides of the marble cave wall. The tensile failure occurred near the opening surface and shear failure at a far distance. The sandstone's overall failure was related to tensile cracking, and splitting failure occurred far away from the opening surface, which was similar to the in situ failure of surrounding rocks during excavation-induced unloading of the high-stress rock mass. The results obtained are instrumental in the construction safety control and prevention of underground engineering disasters.